Successful Treatment of Noise-Induced Hearing Loss by Mesenchymal Stromal Cells: An RNAseq Analysis of Protective/Repair Pathways - Warnecke, Athanasia; Harre, Jennifer; Shew, Matthew; Mellott, Adam J.; Majewski, Igor; Durisin, Martin; Staecker, Hinrich (Frontiers in Cellular Neuroscience, 2021)
Mesenchymal stromal cells (MSCs) are an adult derived stem cell-like population that has been shown to mediate repair in a wide range of degenerative disorders. The protective effects of MSCs are mainly mediated by the release of growth factors and cytokines thereby modulating the diseased environment and the immune system. Within the inner ear, MSCs have been shown protective against tissue damage induced by sound and a variety of ototoxins. To better understand the mechanism of action of MSCs in the inner ear, mice were exposed to narrow band noise. After exposure, MSCs derived from human umbilical cord Wharton’s jelly were injected into the perilymph. Controls consisted of mice exposed to sound trauma only. Forty-eight hours post cell delivery, total RNA was extracted from the cochlea and RNAseq performed to evaluate the gene expression induced by the cell therapy. Changes in gene expression were grouped together based on gene ontology classification. A separate cohort of animals was treated in a similar fashion and allowed to survive for 2 weeks post cell therapy and hearing outcomes determined. Treatment with MSCs after severe sound trauma induced a moderate hearing protective effect. MSC treatment resulted in an upregulation of genes related to immune modulation, hypoxia response, mitochondrial function and regulation of apoptosis. There was a downregulation of genes related to synaptic remodeling, calcium homeostasis and the extracellular matrix. Application of MSCs may provide a novel approach to treating sound trauma induced hearing loss and may aid in the identification of novel strategies to protect hearing.